Deep structure of the Santos Basin‐São Paulo Plateau System, SE Brazil. Issue 8 (26th August 2015) - Evain, M.; Afilhado, A.; Rigoti, C.; Loureiro, A.; Alves, D.; Klingelhoefer, F.; Schnurle, P.; Feld, A.; Fuck, R.; Soares, J.; de Lima, M. Vinicius; Corela, C.; et al.
Abstract The structure and nature of the crust underlying the Santos Basin‐São Paulo Plateau System (SSPS), in the SE Brazilian margin, are discussed based on five wide‐angle seismic profiles acquired during the Santos Basin (SanBa) experiment in 2011. Velocity models allow us to precisely divide the SSPS in six domains from unthinned continental crust (Domain CC) to normal oceanic crust (Domain OC). A seventh domain (Domain D), a triangular shape region in the SE of the SSPS, is discussed by Klingelhoefer et al. (2014). Beneath the continental shelf, a 100 km wide necking zone (Domain N) is imaged where the continental crust thins abruptly from 40 km to less than 15 km. Toward the ocean, most of the SSPS (Domains A and C) shows velocity ranges, velocity gradients, and a Moho interface characteristic of the thinned continental crust. The central domain (Domain B) has, however, a very heterogeneous structure. While its southwestern part still exhibits extremely thinned (7 km) continental crust, its northeastern part depicts a 2–4 km thick upper layer (6.0–6.5 km/s) overlying an anomalous velocity layer (7.0–7.8 km/s) and no evidence of a Moho interface. This structure is interpreted as atypical oceanic crust, exhumed lower crust, or upper continental crust intruded by mafic material, overlying either altered mantle in the first two cases or intruded lower continental crust in the last case. The deep structure and v‐shaped segmentation of the SSPS confirm that an initial episode of rifting occurred there obliquely to the general opening direction of the South Atlantic Central Segment.